Assessing community readiness for early intervention programmes to promote social and emotional health in children. (10th April 2019) - Islam, Shahid; Small, Neil; Bryant, Maria; Bridges, Sally; Hancock, Nicola; Dickerson, Josie
Abstract: Objective: Evidence for early intervention and prevention‐based approaches for improving social and emotional health in young children is robust. However, rates of participation in programmes are low. We explored the dynamics which affect levels of community readiness to address the issues of social and emotional health for pregnant women, young children (0‐4 years) and their mothers. Setting: A deprived inner‐city housing estate in the north of England. The estate falls within the catchment area of a project that has been awarded long‐term funding to address social and emotional health during pregnancy and early childhood. Methods: We interviewed key respondents using the Community Readiness Model. This approach applies a mixed methodology, incorporating readiness scores and qualitative data. A mean community readiness score was calculated enabling the placement of the community in one of nine possible stages of readiness. Interview transcripts were analysed using a qualitative framework approach to generate contextual information to augment the numerical scores. Results: An overall score consistent with vague awareness was achieved, indicating a low level of community readiness for social and emotional health interventions. This score suggests that there will be a low likelihood of participation in programmes that address these issues. Conclusion: Gauging community readiness offers a way of predicting how willing and prepared a community is to address an issue. Modifying implementation plans so that they first address community readiness may improve participation rates.